Assessment of the technical condition of a treatment facility at a chemical enterprise - Tsyhanenko, Liudmyla; Shkromada, Oksana; Volkov, Dmytro; Chekan, Oleksandr; Lutskovskyi, Valerii (Technology audit and production reserves, 2026)
The object of research is a sewage well of a chemical enterprise. The chemical composition of the enterprise’s wastewater, which is concentrated in the averaging unit, and the structural and elemental composition of concrete samples were determined. Upon completion of the experiment, proposals were made regarding the further operation of the chemical enterprise’s treatment plant. It was found that the suspended solids content was higher in the first sample by 4.85%, and in the fifth – by 15.29%. The dry residue content was higher in the second sample by 20.18%, in the fourth – by 9.27%, and in the fifth – by 27.45%. The concentration of ammonium nitrogen is higher in the fourth experiment by 52.31%. The level of ammonium ions was higher in the fourth by 43.77%, nitrite ions in the second and third samples were higher by 16.67%, in the fourth by 383.33%, in the fifth by 983.33%. The increase in nitrate ions in the second sample was by 58.0%, in the third by 146.0%, in the fourth by 276.0%, in the fifth by 520.0%. APAR increased in the second water sample by 306.0%, in the third by 422.0%, in the fourth by 250.0%, in the fifth by 190.0%. The level of total iron is higher in the second group by 2288.89%, in the third – by 970.37%, in the fourth – by 1075.92%, in the fifth – by 1459.26%. The study by the X-ray fluorescence method showed that the CaO content was lower in the first sample by 3.27%, the second – by 2.27%, the third – by 3.01%; Fe2O3 is higher by 20.09%, by 22.77%, by 24.11%, SiO2 by 10.83%, by 2.27%, 3.01%, SO2 was by 4.50%, in the second and third – by 4.05%, TiO2 by 0.68%, by 12.50%, by 14.19%. X-ray diffraction analysis showed the presence of a large amount of gypsum and quartz in the concrete. The conducted research is distinguished by the fact that chemical corrosion of the concrete treatment plant under the influence of wastewater was established. The practical significance of the results obtained is that the destruction of the surface layer of concrete as a result of corrosion was established. Preventive measures are proposed to prevent corrosion of the treatment plant.